Tracking wildfire risk to California railroads: integrating environmental data and railway operations - Karl Kim; Daniele Spirandelli; David Rother; Eric Yamashita; Michelle Toner (Transportation Research Interdisciplinary Perspectives)
Climatic change and wildfire risk have direct implications for the railway industry. Wildfires pose risks to railways in areas with steep topography, sufficient fuels to sustain fire, and meteorological conditions that can ignite large fires. Railway infrastructure and operations also increase the risks of ignition from flammable materials used in track or bridge construction, engine and braking, which can generate sparks, and vegetation management, which can increase fuel for fires. A methodology was developed to identify California railway segments exposed to wildfire risk. Five potential railway segments were identified based on the proximity of the track to areas of burn probability and the relative area for different classes of burn probability. Two segments were selected based on the total area classified as high and very high burn probability and the length of track exposed to very high burn probability. These segments were evaluated regarding land cover, slope, meteorological conditions, and adaptive capacity. Heightened wildfire risk was found in these two segment areas due to complex terrain, meteorological conditions conducive to fire, and large extents of flammable vegetation. The data and methods tested in this study are replicable and scalable and represent initial work in developing a broader vulnerability assessment framework on the exposure, sensitivity, and adaptative capacities of railways exposed to wildfire and other climate hazards at the state or regional level.